Effectiveness of Concentration and Soaking Time of Red Onion Extract on Growth and Flowering Time Roses Cuttings (Rosa centifolia L.) - Annis Indah Larasati; Karno Karno; Syaiful Anwar (University of Prof. Dr. Hazairin, SH, 2023)
The study aimed to examine the effectiveness of the concentration and soaking time of red onion extract on the growth and flowering time of rose cuttings. The test material used 45 stems of roses (Rosa centifolia L.) obtained from community gardens in the Bringin area, Salatiga. The study was conducted with Factorial Randomized Block Design (RBD) for 3 replications. The groups used were based on the raw material for cuttings, such as the upper, middle, and lower stem cuttings. The first factor was the concentration of red onion extract with 5 levels, namely control or concentration of red onion extract 0%, 25%, 50%, 75%, and 100%, and the second factor was soaking time of 4 hours, 6 hours and 8 hours so there is 45 units test. The results showed that a 50% concentration of red onion extract increased the number of shoots, number of leaves, and total fresh weight, a 75% concentration increased flowering time and a 100% concentration increased root length. Soaking time for red onion extract for 6 hours increased root length while soaking time for 8 hours increased the number of leaves. Red onion extract concentration of 75% for 4 hours of soaking time and 50% concentration for 8 hours of soaking time was able to increase the total dry weight of plants.